2011
DOI: 10.4028/www.scientific.net/amr.393-395.481
|View full text |Cite
|
Sign up to set email alerts
|

Thermoplastic Deformation Behavior of 4032 Al Alloy

Abstract: The effect of processing temperature and strain on microstructure and mechanics property of 4032 Al alloy was performed with hot extrusion experiment and finite element method. The results show that the primary silicon distributes more uniformly along with the increase of strain at a certain deformation temperature, and the tensile stress and elongation have less variation. However, elongation decreases obviously when the strain are higher than 70%. At a certain strain, tensile strength increases and elongatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The microstructure shown in Figure 3c corresponds to the HT-Rolled sample subjected to a reduction of the original thickness of 25%. In this micrograph, it can be seen that the acicular eutectic silicon morphology transformed into finer [15] and more evenly distributed particles. Huie Hu et al [13] found similar results under similar conditions of heat treating and rolling.…”
Section: Microstructure and Characterizationmentioning
confidence: 91%
See 1 more Smart Citation
“…The microstructure shown in Figure 3c corresponds to the HT-Rolled sample subjected to a reduction of the original thickness of 25%. In this micrograph, it can be seen that the acicular eutectic silicon morphology transformed into finer [15] and more evenly distributed particles. Huie Hu et al [13] found similar results under similar conditions of heat treating and rolling.…”
Section: Microstructure and Characterizationmentioning
confidence: 91%
“…Temperature also has a great influence on the mechanical properties and microstructure of aluminum alloys. As mentioned by Huie Hu et al [15], tensile strength increases rapidly at processing temperatures between 400 • C and 450 • C, while elongation decreases at temperatures above 400 • C. As for the effect of deformation temperature on the microstructure, a finer grain refinement homogeneously distributed throughout the matrix is achieved for temperatures close to 430 • C; however, at a deformation temperature close to 480 • C, the recrystallized grains undergo coarsening and therefore a not very favorable microstructure, as mentioned by Peng Sun et al [13].…”
Section: Introductionmentioning
confidence: 88%